2020
DOI: 10.1080/20013078.2020.1741176
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles from plasma have higher tumour RNA fraction than platelets

Abstract: In addition to Circulating Tumour Cells (CTCs), cell-free DNA (cfDNA) and Extracellular Vesicles (EVs), the notion of "Tumour-Educated Platelets" (TEP) has recently emerged as a potential source of tumour-derived biomarkers accessible through blood liquid biopsies. Here we sought to confirm the suitability of the platelet blood fraction for biomarker detection in comparison to their corresponding EV fraction. As publications have claimed that tumour RNA and other tumour-derived material are transferred from tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…However, none of the BRAF mutations were detected in platelet-derived RNA samples of these 12 patients while high amounts of wild-type BRAF transcripts were detected. This study concluded that BRAF p.(V600E) mutant transcripts are too rare in the platelet RNA fraction to be reliably detected [41]. So, these findings are similar to our findings for KRAS and both suggest low abundance of tumor derived transcripts in platelets.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, none of the BRAF mutations were detected in platelet-derived RNA samples of these 12 patients while high amounts of wild-type BRAF transcripts were detected. This study concluded that BRAF p.(V600E) mutant transcripts are too rare in the platelet RNA fraction to be reliably detected [41]. So, these findings are similar to our findings for KRAS and both suggest low abundance of tumor derived transcripts in platelets.…”
Section: Discussionsupporting
confidence: 89%
“…The high number of wild type transcripts in platelet samples preclude reliable detection of tumor derived mutant transcripts, which are present at very low copy numbers. A comparative study detected BRAF p.(V600E) in 10 of 12 RNA samples from extracellular vesicles in melanoma patients [41]. However, none of the BRAF mutations were detected in platelet-derived RNA samples of these 12 patients while high amounts of wild-type BRAF transcripts were detected.…”
Section: Discussionmentioning
confidence: 99%
“…As an important biological component of liquid biopsy, exosomes have several advantages compared to TEPs, CTCs and ctDNA. The RNA content of TEPs can likely be affected by therapeutic factors, pathological conditions and activated immune system 60 . CTCs and ctDNA are unstable, fragile and have short half‐lives, leading to the requirement of quick processing after sample collection 9 .…”
Section: The Advantages Of Exosomes As a Liquid Biopsy In Cancer Diagnosis And Prognosismentioning
confidence: 99%
“…Beyond miRNA content, RNA packed in plasma EV has the potential to be used to define tumor mutation landscape, such as BRAF V600E for melanoma, with the aim to detect early-stage disease or define the best clinical approach for certain patients (34). This strategy may be transposed to mutated RNA contained in circulating EV from B-cell malignancies, with the attempt to perform a personalized patient follow-up and therapy.…”
Section: Ev As Biomarkersmentioning
confidence: 99%